Communication Apprehension of Indonesian Students in Sekolah Indonesia Makkah - Sartika, Amalia; Junaedi, Fajar (Jogjakarta Communication Conference (JCC), 2025)
Students at Sekolah Indonesia Makkah (SIM), particularly those who are not proficient in the Indonesian language, face a significant challenge in terms of communication. Sekolah Indonesia Makkah is a school for Indonesian citizens who reside in Makkah. The President of the Islamic Republic of Indonesia established the Sekolah Indonesia Makkah in the Arabian Peninsula. This investigation pertains to the communication breakdown that was experienced by students of the Sekolah Indonesia Makkah. This event has the potential to enhance their academic performance, social interaction, and self-esteem. The purpose of this study is to identify strategies that can be implemented to address the communication crisis within the Sekolah Indonesia Makkah. This study employs the qualitative methods of case study research, which involves data collection through interviews, observation, and documentation. This study examines the strategies employed by educators to assist students in overcoming their challenges, as well as the experiences of students. The results of the study indicate that a supportive learning environment, the implementation of communication techniques, and positive reinforcement based on communication can effectively reduce students' anxiety regarding communication. This study contributes to the development of the theory of communication failure. In conclusion, the results of this study provide recommendations for educational institutions to develop a more inclusive teaching method that supports the growth of student communication, particularly in the context of classroom communication.